The Effect of Company Size, Profitability, and Leverage on Earnings Management with Institutional Ownership as a Moderating Variable in Manufacturing Companies Listed on the Indonesia Stock Exchange in 2020-2024 - Indri Yani; Elfiswandi, Elfiswandi; Lusiana, Lusiana (Jurnal Multidisiplin Sahombu, 2025)
This study aims to determine the effect of Company Size, Profitability, and Leverage on Earnings Management, with Institutional Ownership as a moderating variable. Company Size, Profitability, and Leverage serve as independent variables, while Earnings Management serves as the dependent variable. Institutional Ownership serves as a moderating variable. This study focuses on companies in the Consumer Non-Cyclical Manufacturing Sector listed on the Indonesia Stock Exchange (IDX) for the 2020-2024 period. The sampling method used purposive sampling, resulting in 29 companies from a population of 132. The data were analyzed using panel data analysis techniques.The results show that: (1) Company Size has no significant effect on Earnings Management. (2) Profitability has no significant effect on Earnings Management. (3) Leverage has a significant effect on Earnings Management. (4) Company size does not have a significant effect on earnings management, weakened by institutional ownership as a moderating variable. (5) Profitability has no significant effect on earnings management, weakened by institutional ownership as a moderating variable. (6) Leverage has no significant effect on earnings management, weakened by institutional ownership as a moderating variable.